2016
DOI: 10.1007/s12185-016-2013-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening frequency, incidence and pattern of heparin-induced thrombocytopenia syndrome at a large tertiary institution

Abstract: Increasing awareness and availability of tests for anti-PF4/heparin complex antibodies has raised concerns about indiscriminate testing and inappropriate diagnosis of heparin-induced thrombocytopenia. A retrospective review of HITS testing at a large tertiary centre was performed to determine test patterns and incidence of HITS. Records of anti-PF4 tests over 4 years were reviewed. Positive results were matched against patient medical records and records of heparin utilisation for the diagnosis of HITS. Total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…One Japanese study [19] found a mild decrease in heparin-induced thrombocytopenia (HIT) incidence with LMWH which was 0.6% (0% in patients without central venous catheter, 2.3% in patients with central venous catheter), compared to previous reports with UFH which were 3.9% and 1.0%, respectively [20] and [21]. In the existing study, the group of patients with blood platelets of less than 150,000 /mm3 showed statistically significant improvement in platelet number with shifting to enoxaparin.…”
Section: Discussionmentioning
confidence: 93%
“…One Japanese study [19] found a mild decrease in heparin-induced thrombocytopenia (HIT) incidence with LMWH which was 0.6% (0% in patients without central venous catheter, 2.3% in patients with central venous catheter), compared to previous reports with UFH which were 3.9% and 1.0%, respectively [20] and [21]. In the existing study, the group of patients with blood platelets of less than 150,000 /mm3 showed statistically significant improvement in platelet number with shifting to enoxaparin.…”
Section: Discussionmentioning
confidence: 93%
“…Over the last two decades, a wide range of HIA prevalence in HD has been reported in studies using EIA, ranging from 0 to 47% [ 22 37 , 39 ]. The finding that HIA levels inversely correlate with time on HD helps explain the wide variance as these studies did not standardize time on HD.…”
Section: Discussionmentioning
confidence: 99%
“…It usually challenging in hospitalized patients as majority of the patients will have other causes of thrombocytopenia and also not all physicians are applying the 4Ts score for the pretest probability as recent studies have shown. [5][6][7] The primary objective of this study is to evaluate the frequency of HIT among Sultan Qaboos University Hospital (SQUH) patients and the secondary objective is to assess the utility of the 4T scoring system (which is validated clinical tool that predicts the likelihood of HIT).…”
Section: Introductionmentioning
confidence: 99%